Astrocyte Apoptosis and HIV Replication Are Modulated in Host Cells Coinfected with Trypanosoma cruzi - Urquiza, Javier M.; Burgos, Juan M.; Ojeda, Diego S.; Pascuale, Carla A.; Leguizamón, M. Susana; Quarleri, Jorge F. (Frontiers in Cellular and Infection Microbiology, 2017)
The protozoan Trypanosoma cruzi is the etiological agent of Chagas disease. In immunosuppressed individuals, as it occurs in the coinfection with human immunodeficiency virus (HIV), the central nervous system may be affected. In this regard, reactivation of Chagas disease is severe and often lethal, and it accounts for meningoencephalitis. Astrocytes play a crucial role in the environment maintenance of healthy neurons; however, they can host HIV and T. cruzi. In this report, human astrocytes were infected in vitro with both genetically modified-pathogens to express alternative fluorophore. As evidenced by fluorescence microscopy and flow cytometry, HIV and T. cruzi coexist in the same astrocyte, likely favoring reciprocal interactions. In this context, lower rates of cell death were observed in both T. cruzi monoinfected-astrocytes and HIV-T.cruzi coinfection in comparison with those infected only with HIV. The level of HIV replication is significantly diminished under T. cruzi coinfection, but without affecting the infectivity of the HIV progeny. This interference with viral replication appears to be related to the T. cruzi multiplication rate or its increased intracellular presence but does not require their intracellular cohabitation or infected cell-to-cell contact. Among several Th1/Th2/Th17 profile-related cytokines, only IL-6 was overexpressed in HIV-T.cruzi coinfection exhibiting its cytoprotective role. This study demonstrates that T. cruzi and HIV are able to coinfect astrocytes thus altering viral replication and apoptosis.